Artificial intelligence (AI)-based mobile learning in ELT for EFL learners: The implementation and learners' attitudes - Dini Noor Arini; Fahmi Hidayat; Atiek Winarti; Elsa Rosalina (Lighthouse Publishing, 2022)
Mobile learning powered by artificial intelligence (AI) is a promising vision for transforming education by introducing tutoring systems that can personalize learning. It is being developed to ensure that all learners have the opportunity to be autonomous and to advance collaborative learning. NovoLearning was used in this study to implement mobile learning powered by artificial intelligence (AI). NovoLearning's mobile learning platform powered by artificial intelligence (AI) provides a pleasurable experience and practical language learning for English as a Foreign Language students. Each NovoLearning level includes meaningful learning objectives in the areas of vocabulary, grammar syntax, listening, pronunciation, and role-playing. The purpose of this study was to examine the improvement of English as a Foreign Language (EFL) University students at Universitas Lambung Mangkurat in Indonesia who studied the subject of English using artificial intelligence-based mobile learning. This study used a pretest-posttest non-equivalent control group design, recruiting two groups: one as the control group, which did not use artificial intelligence-based mobile learning, and another as the experimental group, which did. The result indicates that the t critical value (6.373) is greater than the t table, as indicated by the positive values of the lower score (4.4928) and upper score (8.5195). It is less than 0.05 in the Sig (2-tailed) row. Then it can be concluded that the experimental group's English competence was significantly greater than the control group's. Students' positive attitudes toward AI-based mobile learning encompassed two outcomes: (1) increased opportunities for learning for students and (2) NovoLearning areas for improvement during implementation.